Clonal spread of multidrug-resistant Salmonella Kentucky ST198 in poultry market environments in Dhaka city, Bangladesh - Md Abu Sayem Khan; Mahbub Arefin Rafi; Md Azad Hossen; Md. Majibur Rahman; Sabita Rezwana Rahman (PLoS ONE, 2026)
Salmonella enterica serovar Kentucky ST198 is a globally distributed, multidrug-resistant clone with growing concern due to its zoonotic potential. Despite its detection in Bangladesh from poultry, migratory birds, and fish, genomic data from poultry remain limited which is its main reservoir. This study aimed to characterize poultry-derived S. Kentucky ST198 isolates from live bird markets in Dhaka and compare them with strains from migratory birds and fish to assess clonal diversity, resistance profiles, and transmission characteristics. Five isolates recovered from poultry carcasses and slaughterhouse environments from three markets were confirmed as S. Kentucky ST198 by whole genome sequencing. All showed resistance to ciprofloxacin, aminoglycosides, sulfonamides, and tetracyclines, supported by the presence of acquired resistance genes ( aadA7, aac(3)-Id, aac(6′)-Iaa, sul1, tet(A), blaTEM-1B ) and mutations in gyrA (S83F) and parC (S80I). Core-genome SNP analysis revealed that the five poultry isolates differed by only 0–4 SNPs, indicating recent transmission or a shared source within the poultry distribution network. To explore broader ecological links, these genomes were compared with 15 Bangladeshi ST198 genomes from migratory birds and fish. All genomes showed similar antimicrobial resistance and virulence genes profiles, with variable presence of SPI-4, plasmid replicons and integrons. Combined results from pan-genome analysis, core-genome phylogeny, and principal component analysis (PCA) indicated distinct source-associated clustering: poultry isolates formed a tightly clustered, highly clonal group; migratory bird isolates were more dispersed; and fish isolates formed a separate cluster. The open nature of the pan-genome further suggested ongoing gene acquisition within this population. Globally, Bangladeshi isolates formed a monophyletic clade, indicating a locally maintained lineage circulating across environmental and animal reservoirs. Collectively, these findings represent the local circulation of a clonal MDR S. Kentucky ST198 lineage across poultry and non-poultry sources and highlight the need for genomic surveillance in high-risk settings such as live bird markets.